Radiation situation on the territory of the peaceful nuclear explosion «Globus-1» before performing the rehabilitation works - E. V. Khramtsov (Радиационная гигиена)
The article provides data on the radiation situation on research results 2008and 2014 in the area adjacent to the site of the peaceful nuclear explosion “Globus-1” before the rehabilitation works (2014—2015), made with a view to removing accidental contamination. The results of the analysis of the dynamics of changes of the radiation situation during the period from 2008 to 2014 year and assess the radiological situation on basic indicators: the values of the dose of technogenic radionuclides content in soil, water and other objects in the environment. On the basis of the research shows that the radiation situation on the territory of the “Globuc-1” has not undergone significant changes from 2008 onwards. An additional dose of man-made exposure of individuals from the population is formed mainly due to external irradiation provided temporary residence on the territory with elevated levels of gamma radiation. As a result of work performed by sealing research wells decreased stem onto the surface of the water with high concentrations of cesium-137, strontium-90 and tritium. Radioactive contamination of the soil to a depth of 1 m, studied in the year 2014, is estimated at 2200 m3 and can be classified as very active and low-level radioactive wastes for which allowed a near-surface burial. Because of the inaccessibility of the area for the removal of soil and remoteness from populated areas considered advisable to arrange the near-surface burial of contaminated soil () directly on the premises of the site.